Microstructural design of ceramics for bone regeneration. Issue 7 (July 2020) - del Valle García, Adrián; Hautcoeur, Dominique; Leriche, Anne; Cambier, Francis; Baudín, Carmen
Abstract: Dense tricalcium phosphate, Ca3 (PO4 )2 (TCP) – diopside, CaMg(SiO3 )2, composites present better mechanical properties than single phase TCP. In this work, it is investigated whether the mechanical behaviour improvement by diopside is maintained in porous scaffolds. The processing parameters to obtain cylinders with ≈ 50% of aligned pores of elliptical cross sections with major axis up to 100 μm by freeze casting and sintering were established. Pore channels were introduced in the green specimens by laser ablation. After sintering, the diameter of the cross sections of the channels was ≈ 700 μm. The ceramic composite microstructure was constituted by a substructure of small diopside particles (2 −7 μm) and dense β-TCP zones of larger dimensions (up to 40 μm). Strength values, determined by diametral compression (DCDT) (≈ 2.5–4 MPa) are in the range of strength of cancellous bone. Diopside presents transgranular fracture, hindering crack propagation from the β-TCP areas and the pores, as occurred in the dense materials.